[Ru(Bi8)2]6+ – A Cluster in a Highly Disordered Crystal Structure is the Key to the Understanding of the Coordination Chemistry of Bismuth Polycations12. Issue 14 (20th September 2013) - Groh, Matthias F.; Isaeva, Anna; Frey, Christoph; Ruck, Michael
Abstract Black platelets of Bi39.67(7)Ru2Br35.0(2) were crystallized from a melt of Bi, BiBr3, and Ru. In the tetragonal crystal structure [P4/mbm, a = 1311.92(6) pm, c = 3018.2(4) pm at 155(5) K], cluster cations [(Bi82+)Ru2+(Bi82+)] are embedded in a matrix of disordered bromido‐bismuthate(III) groups. A thorough analysis of the disorder in the anionic part enabled the unambiguous assignment of the cluster charge. The η4‐coordination of the two Bi82+ square antiprisms to the RuII atom in the sandwich complex resembles the bonding of Bi5+ and Bi82+ in the clusters [(Bi5+)Ru+(Bi4Br4)Ru+(Bi5+)] and [(Bi82+)Ru+(Bi4Br4)Ru+(Bi5+)] as well as of Bi42– in <![CDATA[$\rm^{1}_{\infty}$]]> <inline-graphic xlink:href="ark:/27927/pgg4t8k1k7j" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />[(Bi42–)Ru+(Bi4Br4)Ru+]. By combining crystal chemical considerations for all mentioned compounds and using quantum chemical calculations, a common bonding scheme for the coordination compounds of bismuth polycations and polyanions was established. The η4‐coordinating bismuth polycations and polyanions act as six electron donors, comparable to nido‐carborane ligands, Zintl anions E94– and E56– (E = Si to Pb), cyclopentadienyl ligands, or the cyclobutadiene dianion. The electron count for the transition metal is 18 in all finite clusters.